OXYGEN CONSUMPTION OF SCALLOP PECTEN MAXIMUS IN DIFFERENT PHYSIOLOGICAL CONDITION - Djoko Suprapto (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The level of oxygen consumption is one of the indicators of organism physiological condition. It can be used to understand the energetical flow of the organism and finally some measures can be take to manipulate the environmental condition in order to give the optimum environment to grow. A semi open system or semi running system was used to measure the oxygen consumption. The principle of the measurement was to calculate the difference between the oxygen concentration of water entering respiratory chambers with the one out of respiratory chambers. The experiment was using Pecten maximus coming from Brest, Scotland, Ireland, and Saint Brieux. Each population showing difference rate of oxygen consumption, meanwhile oxygen consumption influenced by bodyweight and other physiological conditions. Scotland population having the best performance of energetical balance, compared with the other three population.